Rice Seeds as Biofactories of Rationally Designed and Cell-Penetrating Antifungal PAF Peptides - Bundó, Mireia; Shi, Xiaoqing; Vernet, Mar; Marcos, Jose F.; López-García, Belén; Coca, María (Frontiers in Plant Science, 2019)
PAFs are short cationic and tryptophan-rich synthetic peptides with cell penetrating antifungal activity. They show potent and selective killing activity against major fungal pathogens, and low toxicity to other eukaryotic and bacterial cells. These properties make them a promising alternative to fulfill the need of novel antifungals with potential applications in crop protection, food preservation and medical therapies. However, the difficulties of cost-effective manufacturing of PAFs by chemical synthesis or biotechnological production in microorganisms have hampered their development for practical use. This work explores the feasibility of using rice seeds as an economical and safe production system of PAFs. The rationally designed PAF102 peptide with improved antifungal properties was selected for assessing PAF biotechnological production. Two different strategies are evaluated: (i) the production as a single peptide targeted to protein bodies; and (ii) the production as an oleosin fusion protein targeted to oil bodies. Both strategies are designed to offer stability to the PAF peptide in the host plant and to facilitate its downstream purification. Our results demonstrate that PAF does not accumulate to detectable levels in rice seeds when produced as a single peptide, whereas it is successfully produced as fusion protein to the Oleosin18, up to 20 µg of peptide per gram of grain. We show that the expression of the chimeric Ole18-PAF102 gene driven by the Ole18 promoter results in the specific accumulation of the fusion protein in the embryo and aleurone layer of the rice seed. Ole18-PAF102 accumulation has no deleterious effects on seed yield, germination capacity, or seedling growth. We also show that the Oleosin18 protein serves as carrier to target the fusion protein to oil bodies facilitating PAF102 recovery. Importantly, the recovered PAF102 is active against the fungal phytopatogen Fusarium proliferatum. Altogether, our results prove that the oleosin fusion technology allows the production of PAF bioactive peptides to assist the exploitation of these antifungal compounds.